Survey of primordial and altered carbonaceous chondrite clasts in Howardites - Isa, Junko; Nakato, Aiko; Kanemaru, Rei; Yamaguchi, Akira; Noguchi, Takaaki (2023)
The 14th Symposium on Polar Science/Ordinary sessions [OA] Antarctic Meteorite, Tue. 14 Nov. / 3F Multipurpose Conference room, Institute of Statistical Mathematics conference object